PENGARUH PENGARUH SERVICESCAPE,VALUE,IMAGE,PLEASURE, TERHADAP BEHAVIORAL INTENTIONSPADA HOTEL BINTANG 4 DI SURABAYA - Istiana Raswini; Siti Rahayu; Fitri Novika Widjaja (Perpustakaan Universitas Surabaya, 2018)
This study aims to determine and analyze the influence of the factors Servicescape, Perceived Value, Image, Pleasure, to Behavioral Intention at 4 star hotels in Surabaya. In the previous study is still relevant to be used at this time. The object taken is a 4 star hotel in Surabaya.The data used in this study is the primary data obtained from the distribution of questionnaires. Respondents in this study were 150 respondents who had visited the 4 star hotel in Surabaya, had used the facilities at the hotel, and had visited 4 star hotels in other cities. The sampling technique of this research is convenience sampling. This study uses a quantitative approach with statistical testing. The test was performed using Structural Equation Modeling (SEM) method with the help of Analysis of moment structures (AMOS 22).The results of this study indicate that there is a significant relationship between Servicescape to Perceived Value, Servicescape to Image, Servicescape to pleasure, Perceived Value to Pleasure, Perceived Value to Behavioral Intention, Image to Pleasure, Image to Behavioral Intention, Pleasure to Behavioral Intention.